Translucent polyolefin blends for excellent impact-stiffness balance and flow
By adjusting the ratio and characteristics of the heterogeneous propylene ethylene copolymer and the ethylene polymer in the heterogeneous polypropylene composition, the problem of difficult balance of optical and mechanical characteristics in the prior art is solved, and a composition with high light transmittance and good mechanical properties is achieved.
Patent Information
- Application Number
- CN202180060628.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-07-16
- Filing Date
- 2021-07-08
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-07-08
AI Technical Summary
Existing heterophase polypropylene compositions are difficult to achieve a beneficial balance between optical and mechanical properties in automotive applications, especially in terms of total light transmittance and impact properties.
Using a heterophase polypropylene composition comprising the first heterophase propylene ethylene copolymer (HECO1), a second heterophase propylene ethylene copolymer (HECO2) and an ethylene polymer (PE), the crystalline fraction, soluble fraction and melt flow rate of the composition are optimized to achieve good overall light transmittance and mechanical properties by adjusting the proportion and characteristics of each component.
The advantageous balance of stiffness and impact strength of the heterogeneous polypropylene composition is achieved, while maintaining a good overall light transmittance, which is suitable for demanding applications such as automobiles.
Smart Images

Figure BDA0004113791220000111 
Figure BDA0004113791220000112 
Figure BDA0004113791220000113
Abstract
Description
Technical Field
[0001] The present invention relates to heterophasic polypropylene compositions having good overall light transmittance and a beneficial balance of stiffness and impact properties, and articles made therefrom. Background Art
[0002] Polymers (such as polypropylene) are increasingly used in different demanding applications. Meanwhile, people are constantly looking for custom polymers that meet these application requirements. These requirements may be challenging because many polymer properties are directly or indirectly related, i.e. improving a particular property may only be achieved at the expense of another property. For example, rigidity can be improved by increasing the relative amount of crystallinity and / or homopolymer in the composition. As a result, the material becomes more brittle, thereby resulting in poor impact properties. It is known that the impact strength of polypropylene can be improved by dispersing the rubber phase in the polymer matrix to obtain a heterophasic polypropylene composition.
[0003] Such heterophasic propylene copolymers comprise a matrix which is a propylene homopolymer or a random propylene copolymer, in which an amorphous phase comprising a propylene copolymer rubber (elastomer) is dispersed. Thus, the polypropylene matrix comprises (finely) dispersed inclusions which do not belong to the matrix and which comprise the elastomer. The term inclusions indicates that the matrix and the inclusions form different phases within the heterophasic propylene copolymer, which inclusions are visible, for example, by high-resolution microscopy, such as electron microscopy, scanning force microscopy or atomic force microscopy.
[0004] Heterophasic polypropylene compositions have long been used in automotive applications because they have beneficial mechanical properties, including a beneficial balance of stiffness and impact strength (as indicated by simply supported beam or Izod impact strength parameters and puncture energy). Sensors and light emitting diodes (LEDs) have been used in automobiles for many years, but due to emerging trends such as autonomous driving, more and more sensors need to be integrated into vehicles in the near future. For aesthetic reasons, sensors and / or LEDs are preferably invisible to the naked eye, but the function (sensing or luminescence) of the components should not be compromised. Therefore, translucent polypropylene blends have great potential for application in such systems. However, there is still a need for translucent polypropylene blends having optimal mechanical properties in addition to suitable optical properties.
[0005] There are many disclosures about heterophasic polypropylene compositions for automotive applications, but the object of the present invention, namely obtaining a beneficial balance of optical (especially total light transmittance) and mechanical properties (especially impact properties), has not been adequately addressed.
[0006] WO 2017 / 117054 A1 discloses blends of heterophasic propylene ethylene copolymers with propylene homopolymers to obtain improved haze properties, however no indication of total light transmittance is given.
[0007] EP 2 275 485 A1 describes a heterophasic polypropylene composition having improved mechanical properties, but in particular using 10 wt. % of mineral fillers.
[0008] EP 2 480 606 A1 describes a heterophasic polypropylene composition having a high melt flow rate and a low C2 content. Summary of the invention
[0009] The present invention is based on the finding that a heterophasic polypropylene composition (C) comprising a first heterophasic propylene ethylene copolymer (HECO1), a second heterophasic propylene ethylene copolymer (HECO2) and an ethylene polymer (PE) has an improved balance of stiffness and impact strength and a good total light transmittance while maintaining otherwise favourable properties, such as processability.
[0010] The present invention relates to a heterophasic polypropylene composition (C) comprising:
[0011] a. 60.0 to 85.0 wt.% of a first heterophasic propylene ethylene copolymer (HECO1) having:
[0012] i. Crystalline fraction (CF) determined according to CRYSTEX QC method ISO 6427-B, relative to the total
[0013] weight, which is in the range of 75.0 to 92.0 wt %;
[0014] ii. Soluble fraction (SF) determined according to CRYSTEX QC method ISO 6427-B, relative to the total
[0015] weight, which is present in an amount ranging from 8.0 to 25.0 weight %;
[0016] iii. the intrinsic viscosity (IV(SF)) of the soluble fraction is in the range of 2.00 to 4.00 dl / g;
[0017] b. 5.0 to 20.0 wt. % of a second heterophasic propylene ethylene copolymer (HECO2), which is different from the first heterophasic propylene ethylene copolymer (HECO1), having
[0018] i. Soluble fraction (SF) determined according to CRYSTEX QC method ISO 6427-B, relative to the total HECO2
[0019] weight, which is present in an amount ranging from 15.0 to 30.0 weight %;
[0020] ii. the intrinsic viscosity (IV(SF)) of the soluble fraction is in the range of 2.5 to 5.0 dl / g; and
[0021] c. 5.0 to 20.0 wt% of an ethylene polymer (PE) selected from ethylene-based plastomers and LDPE having a molecular weight of 895 to 925 kg / m 3 Density within range;
[0022] wherein the heterophasic polypropylene composition (C) has a melt flow rate MFR2 measured according to ISO 1133-1 at 230 °C and a load of 2.16 kg in the range of 15.0 to 40.0 g / 10 min, and the soluble fraction (SF) determined according to CRYSTEX QC method ISO 6427-B is present in an amount in the range of 5.0 to 23.0 wt.-% relative to the total weight of the heterophasic polypropylene composition (C), and
[0023] wherein the combined amount of the first heterophasic propylene ethylene copolymer (HECO1), the second heterophasic propylene ethylene copolymer (HECO2) and the ethylene polymer (PE) is greater than or equal to 95 wt.-% relative to the total weight of the heterophasic polypropylene composition (C).
[0024] In another aspect the present invention is an injection moulded article comprising the heterophasic polypropylene composition (C) as described above, preferably wherein the injection moulded article is an automotive article.
[0025] definition
[0026] Polymer blend refers to a mixture of two or more polymer components. Generally, blends can be prepared by mixing two or more polymer components. Suitable mixing procedures known in the art are in-situ blending and post-polymerization blending during polymerization. During in-situ blending, polymer components produced in different stages of a multi-stage polymerization process are blended by polymerizing a polymer component in the presence of another polymer component polymerized in the previous stage. Post-polymerization blending can be a dry blend of polymer components such as polymer powders and / or compounded polymer pellets or a melt blending of melt-mixed polymer components. In the present invention, polymer blends are preferably prepared by post-polymerization blending of polymer components.
[0027] Heterophasic polypropylene is a propylene-based copolymer having a crystalline matrix phase, which can be a propylene homopolymer or a random copolymer of propylene and at least one α-olefin comonomer, and an elastomeric phase dispersed therein. In the case of a random heterophasic propylene copolymer, the crystalline matrix phase is a random copolymer of propylene and at least one α-olefin comonomer.
[0028] The elastomeric phase may be a propylene copolymer with a high amount of comonomer which is not randomly distributed in the polymer chain but is distributed in comonomer-rich block structures and propylene-rich block structures. Heterophasic polypropylene generally differs from monophasic propylene copolymers as it shows two different glass transition temperatures Tg, which are attributed to the matrix phase and the elastomeric phase.
[0029] A plastomer is a polymer that combines the properties of elastomers and plastics, such as rubber-like properties and the processability of plastics. Ethylene-based plastomers are plastomers having a molar majority of ethylene monomer units.
[0030] Although low-density polyethylene (LDPE) does have a low density characteristic (usually 910 to 940 kg / m 3 ), but in the context of the present invention, the characteristics of LDPE are the result of a high pressure free radical polymerization process and therefore have a significantly branched nature, in contrast to linear low density polyethylene (LLDPE), which has a similar low density without branching characteristics due to the use of transition metal-based polymerization catalysts. DETAILED DESCRIPTION
[0031] The instant heterophasic polypropylene composition (C) comprises a first heterophasic propylene ethylene copolymer (HECO1), a second heterophasic propylene ethylene copolymer (HECO2) and an ethylene polymer (PE), each having the properties given in the following sections and in the amounts specified below.
[0032] The first heterophasic propylene ethylene copolymer (HECO1)
[0033] The first heterophasic propylene ethylene copolymer (HECO1) according to this invention is present in an amount in the range of 60.0 to 85.0 wt.-%, more preferably in an amount in the range of 65.0 to 82.0 wt.-%, still more preferably in an amount in the range of 70.0 to 80.0 wt.-%, most preferably in an amount in the range of 74.0 to 78.0 wt.-%, relative to the total weight of the heterophasic polypropylene composition (C).
[0034] The first heterophasic propylene ethylene copolymer (HECO1) has a crystalline fraction (CF) determined according to CRYSTEX QC method ISO 6427-B, which is present in an amount in the range of 75.0 to 92.0 wt.-%, more preferably in the range of 78.0 to 90.0 wt.-%, still more preferably in the range of 81.0 to 88.0 wt.-%, most preferably in the range of 83.0 to 86.0 wt.-%, relative to the total weight of the first heterophasic propylene ethylene copolymer (HECO1).
[0035] The intrinsic viscosity (IV(CF)) of the crystalline fraction (CF) of the first heterophasic propylene ethylene copolymer (HECO1) is preferably in the range of 1.00 to 2.00 dl / g, more preferably in the range of 1.10 to 1.80 dl / g, still more preferably in the range of 1.20 to 1.60 dl / g, most preferably in the range of 1.25 to 1.50 dl / g.
[0036] The crystalline fraction (CF) of the first heterophasic propylene ethylene copolymer (HECO1) preferably has an ethylene content (C2(CF)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 0.5 to 5.0 wt.-%, more preferably in the range of 1.0 to 4.0 wt.-%, still more preferably in the range of 1.3 to 3.0 wt.-%, most preferably in the range of 1.5 to 2.0 wt.-%.
[0037] The first heterophasic propylene ethylene copolymer (HECO1) has a soluble fraction (SF) determined according to CRYSTEX QC method ISO 6427-B, which is present in an amount in the range of 8.0 to 25.0 wt.-%, more preferably in the range of 10.0 to 22.0 wt.-%, still more preferably in the range of 12.0 to 19.0 wt.-%, most preferably in the range of 14.0 to 17.0 wt.-%, relative to the total weight of the first heterophasic propylene ethylene copolymer (HECO1).
[0038] The intrinsic viscosity (IV(SF)) of the soluble fraction (SF) of the first heterophasic propylene ethylene copolymer (HECO1) is in the range of 2.00 to 4.00 dl / g, more preferably in the range of 2.30 to 3.70 dl / g, still more preferably in the range of 2.50 to 3.50 dl / g, most preferably in the range of 2.60 to 3.30 dl / g.
[0039] The soluble fraction (SF) of the first heterophasic propylene ethylene copolymer (HECO1) preferably has an ethylene content (C2(CF)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 20.0 to 60.0 wt.-%, more preferably in the range of 25.0 to 50.0 wt.-%, still more preferably in the range of 30.0 to 40.0 wt.-%, most preferably in the range of 34.0 to 38.0 wt.-%.
[0040] The ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction (IV(SF) / IV(CF)) of the first heterophasic propylene ethylene copolymer (HECO1) is preferably in the range of 1.00 to 3.00, more preferably in the range of 1.30 to 2.70, still more preferably in the range of 1.60 to 2.40, most preferably in the range of 1.80 to 2.20.
[0041] The first heterophasic propylene ethylene copolymer (HECO1) preferably has a xylene cold soluble fraction (XCS), measured at 25 °C according to ISO 16152, present in an amount in the range of 8.0 to 25.0 wt.-%, more preferably in the range of 10.0 to 22.0 wt.-%, still more preferably in the range of 12.0 to 19.0 wt.-%, most preferably in the range of 14.0 to 17.0 wt.-%, relative to the total weight of the first heterophasic propylene ethylene copolymer (HECO1).
[0042] The intrinsic viscosity (IV(XCS)) of the xylene cold soluble fraction (XCS) of the first heterophasic propylene ethylene copolymer (HECO1) is preferably in the range of 2.00 to 4.00 dl / g, more preferably in the range of 2.30 to 3.70 dl / g, still more preferably in the range of 2.50 to 3.40 dl / g, most preferably in the range of 2.70 to 3.30 dl / g.
[0043] The xylene cold soluble fraction (XCS) of the first heterophasic propylene ethylene copolymer (HECO1) preferably has an ethylene content (C2(XCS)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 20.0 to 60.0 wt.-%, more preferably in the range of 25.0 to 50.0 wt.-%, still more preferably in the range of 30.0 to 45.0 wt.-%, most preferably in the range of 35.0 to 40.0 wt.-%.
[0044] The total ethylene content (C2) of the first heterophasic propylene ethylene copolymer (HECO1) is preferably measured in the range of 3.0 to 15.0 wt.-%, more preferably in the range of 4.0 to 12.0 wt.-%, still more preferably in the range of 5.0 to 10.0 wt.-%, most preferably in the range of 6.0 to 8.0 wt.-%.
[0045] The melt flow rate MFR2 of the first heterophasic propylene ethylene copolymer (HECO1) measured according to ISO 1133-1 at 230°C and a load of 2.16 kg is preferably in the range of 15.0 to 50.0 g / 10 min, more preferably in the range of 20.0 to 45.0 g / 10 min, still more preferably in the range of 25.0 to 43.0 g / 10 min, most preferably in the range of 30.0 to 40.0 g / 10 min.
[0046] The first heterophasic propylene ethylene copolymer (HECO1) can be polymerized by methods well known in the art, or alternatively can be a commercially available polypropylene product. It should be understood that commercial products may contain common additives and nucleating agents, which may contribute to the total ash content of the heterophasic polypropylene composition (C).
[0047] Second heterophasic propylene ethylene copolymer (HECO2)
[0048] The second heterophasic propylene ethylene copolymer (HECO2) is different from the first heterophasic propylene ethylene copolymer (HECO1), meaning that at least one of the properties defining the heterophasic propylene ethylene copolymers HECO1 and HECO2 must be different.
[0049] The second heterophasic propylene ethylene copolymer (HECO2) according to this invention is present in an amount in the range of 5.0 to 20.0 wt.-%, more preferably in an amount in the range of 7.0 to 18.0 wt.-%, still more preferably in an amount in the range of 9.0 to 16.0 wt.-%, most preferably in an amount in the range of 10.0 to 14.0 wt.-%, relative to the total weight of the heterophasic polypropylene composition (C).
[0050] The melt flow rate MFR2 of the second heterophasic propylene ethylene copolymer (HECO2) measured according to ISO 1133-1 at 230°C and a load of 2.16 kg is preferably in the range of 1.0 to 20.0 g / 10 min, more preferably in the range of 2.0 to 17.0 g / 10 min, still more preferably in the range of 3.0 to 15.0 g / 10 min, most preferably in the range of 4.0 to 13.0 g / 10 min.
[0051] The total ethylene content (C2) of the second heterophasic propylene ethylene copolymer (HECO2) is preferably measured in the range of 8.0 to 15.0 wt.-%, more preferably in the range of 9.0 to 13.0 wt.-%, still more preferably in the range of 9.5 to 12.0 wt.-%, most preferably in the range of 10.0 to 11.5 wt.-%.
[0052] The second heterophasic propylene ethylene copolymer (HECO2) has a soluble fraction (SF) determined according to CRYSTEX QC method ISO 6427-B, which is present in an amount in the range of 15.0 to 30.0 wt.-%, more preferably in the range of 17.0 to 28.0 wt.-%, still more preferably in the range of 19.0 to 26.0 wt.-%, most preferably in the range of 20.0 to 24.0 wt.-%, relative to the total weight of the second heterophasic propylene ethylene copolymer (HECO2).
[0053] The intrinsic viscosity (IV(SF)) of the soluble fraction (SF) of the second heterophasic propylene ethylene copolymer (HECO2) is in the range of 2.50 to 5.00 dl / g, more preferably in the range of 2.70 to 4.00 dl / g, still more preferably in the range of 2.90 to 3.50 dl / g, most preferably in the range of 3.10 to 3.40 dl / g.
[0054] The soluble fraction (SF) of the second heterophasic propylene ethylene copolymer (HECO2) preferably has an ethylene content (C2(CF)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 20.0 to 60.0 wt.-%, more preferably in the range of 25.0 to 50.0 wt.-%, still more preferably in the range of 30.0 to 45.0 wt.-%, most preferably in the range of 35.0 to 40.0 wt.-%.
[0055] The second heterophasic propylene ethylene copolymer (HECO2) thus has a crystalline fraction (CF), determined according to CRYSTEX QC method ISO 6427-B, present in an amount in the range of 70.0 to 85.0 wt.-%, more preferably in the range of 72.0 to 83.0 wt.-%, still more preferably in the range of 74.0 to 81.0 wt.-%, most preferably in the range of 76.0 to 80.0 wt.-%, relative to the total weight of the second heterophasic propylene ethylene copolymer (HECO2).
[0056] The intrinsic viscosity (IV(CF)) of the crystalline fraction (CF) of the second heterophasic propylene ethylene copolymer (HECO2) is preferably in the range of 1.00 to 2.50 dl / g, more preferably in the range of 1.20 to 2.30 dl / g, still more preferably in the range of 1.40 to 2.20 dl / g, most preferably in the range of 1.50 to 2.10 dl / g.
[0057] The crystalline fraction (CF) of the second heterophasic propylene ethylene copolymer (HECO2) preferably has an ethylene content (C2(CF)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 0.5 to 7.0 wt.-%, more preferably in the range of 1.5 to 6.0 wt.-%, still more preferably in the range of 2.0 to 5.0 wt.-%, most preferably in the range of 2.5 to 4.5 wt.-%.
[0058] The ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction (IV(SF) / IV(CF)) of the second heterophasic propylene ethylene copolymer (HECO2) is preferably in the range of 1.00 to 3.00, more preferably in the range of 1.30 to 2.70, still more preferably in the range of 1.40 to 2.40, most preferably in the range of 1.50 to 2.10.
[0059] The first heterophasic propylene ethylene copolymer (HECO2) preferably has a xylene cold soluble fraction (XCS), determined according to ISO 16152B, present in an amount in the range of 15.0 to 30.0 wt.-%, more preferably in the range of 17.0 to 28.0 wt.-%, still more preferably in the range of 19.0 to 26.0 wt.-%, most preferably in the range of 21.0 to 24.0 wt.-%, relative to the total weight of the second heterophasic propylene ethylene copolymer (HECO2).
[0060] The intrinsic viscosity (IV(XCS)) of the xylene cold soluble fraction (XCS) of the second heterophasic propylene ethylene copolymer (HECO2) is preferably in the range of 2.50 to 5.00 dl / g, more preferably in the range of 2.80 to 4.50 dl / g, still more preferably in the range of 3.10 to 4.00 dl / g, most preferably in the range of 3.40 to 3.80 dl / g.
[0061] The xylene cold soluble fraction (XCS) of the second heterophasic propylene ethylene copolymer (HECO2) preferably has an ethylene content (C2(XCS)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 20.0 to 60.0 wt.-%, more preferably in the range of 25.0 to 50.0 wt.-%, still more preferably in the range of 30.0 to 50.0 wt.-%, most preferably in the range of 33.0 to 48.0 wt.-%.
[0062] The ratio of the melt flow rates MFR2 measured according to ISO 1133-1 at 230°C and a load of 2.16 kg (MFR2(HECO1) / MFR2(HECO2)) of the first and second heterophasic propylene ethylene copolymers is preferably at least 2.0, more preferably in the range of 2.0 to 20.0, still more preferably in the range of 2.30 to 16.0, still more preferably in the range of 2.60 to 13.0, most preferably in the range of 2.90 to 10.0.
[0063] The second heterophasic propylene ethylene copolymer (HECO2) can be polymerized by methods well known in the art, or alternatively can be a commercially available polypropylene product. It should be understood that commercial products may contain common additives and nucleating agents, which may contribute to the total ash content of the heterophasic polypropylene composition (C).
[0064] Ethylene polymer (PE)
[0065] The ethylene polymer (PE) according to this invention is present in an amount in the range of 5.0 to 20.0 wt.-%, more preferably in an amount in the range of 6.0 to 17.0 wt.-%, still more preferably in an amount in the range of 7.0 to 14.0 wt.-%, most preferably in an amount in the range of 8.0 to 12.0 wt.-%, relative to the total weight of the heterophasic polypropylene composition (C).
[0066] The density of ethylene polymer (PE) is between 895 and 925 kg / m 3 In the range of 989 to 922 kg / m 3 In the range of 900 to 919 kg / m 3 In the range of 901 to 917 kg / m 3 within the range.
[0067] The melt flow rate MFR2 of the ethylene polymer (PE) measured at 190°C and a load of 2.16 kg according to ISO 1133-1 is preferably in the range of 0.5 g / 10min to 30.0 g / 10min, more preferably in the range of 0.6 to 25.0 g / 10min, still more preferably in the range of 0.8 to 20.0 g / 10min, most preferably in the range of 1.0 to 18.0 g / 10min.
[0068] In the broadest sense, the ethylene polymer (PE) may be selected from any low density polyethylene or ethylene-based plastomer satisfying the above-mentioned properties.
[0069] In a preferred embodiment, the ethylene polymer (PE) is a low density polyethylene (LDPE).
[0070] In said embodiment, the melt flow rate MFR2 of the low density polyethylene (LDPE) measured at 190°C and a load of 2.16 kg according to ISO 1133-1 is preferably in the range of 10.0 g / 10min to 30.0 g / 10min, more preferably in the range of 11.0 to 25.0 g / 10min, still more preferably in the range of 12.0 to 20.0 g / 10min, and most preferably in the range of 13.0 to 18.0 g / 10min.
[0071] In the embodiment, the density of the low density polyethylene (LDPE) is preferably between 908 and 925 kg / m 3 In the range of 910 to 922 kg / m 3 In the range of 912 to 919 kg / m 3 In the range of 913 to 917 kg / m 3 within the range.
[0072] In an alternative embodiment, the ethylene polymer (PE) is an ethylene-based plastomer (PL).
[0073] In said embodiment, the melt flow rate MFR2 of the ethylene-based plastomer (PL) measured at 190°C and a load of 2.16 kg according to ISO 1133-1 is preferably in the range of 0.5 g / 10 min to 10.0 g / 10 min, more preferably in the range of 0.6 to 7.0 g / 10 min, still more preferably in the range of 0.8 to 5.0 g / 10 min, and most preferably in the range of 1.0 to 3.0 g / 10 min.
[0074] In the embodiment described, the density of the ethylene-based plastomer (PL) is preferably in the range of 895 to 908 kg / m 3 In the range of 989 to 906 kg / m 3 In the range of 900 to 905 kg / m 3 In the range of 901 to 904 kg / m 3 within the range.
[0075] In said embodiment, the ethylene-based plastomer (PL) preferably comprises a comonomer selected from C3 to C10 alpha olefins, more preferably from C4 to C8 alpha olefins, still more preferably from 1-hexene or 1-octene, most preferably 1-octene.
[0076] It is particularly preferred that the ethylene-based plastomer (PL) comprises 1-octene as the only comonomer.
[0077] In the described embodiment, the ethylene-based plastomer is quantitatively 13 The comonomer content measured by C-NMR analysis is in the range of 3.0 to 6.0 mol %, more preferably in the range of 4.0 to 5.5 mol %, still more preferably in the range of 4.3 to 5.3 mol %, most preferably in the range of 4.5 to 5.0 mol %.
[0078] The ethylene polymer (PE) may be polymerized by methods well known in the art or alternatively may be a commercial polyethylene product. It is understood that commercial products may contain common additives and nucleating agents which may contribute to the total ash content of the heterophasic polypropylene composition (C).
[0079] Heterophasic polypropylene composition (C)
[0080] The heterophasic polypropylene composition (C) according to this invention comprises 60.0 to 85.0 wt% of a first heterophasic propylene ethylene copolymer (HECO1), 5.0 to 20.0 wt% of a second heterophasic propylene ethylene copolymer (HECO2) and 5.0 to 20.0 wt% of an ethylene polymer (PE).
[0081] In a preferred embodiment the heterophasic polypropylene composition (C) comprises 65.0 to 82.0 wt% of a first heterophasic propylene ethylene copolymer (HECO1), 7.0 to 18.0 wt% of a second heterophasic propylene ethylene copolymer (HECO2) and 6.0 to 17.0 wt% of an ethylene polymer (PE).
[0082] In another preferred embodiment the heterophasic polypropylene composition (C) comprises 70.0 to 80.0 wt.% of a first heterophasic propylene ethylene copolymer (HECO1), 9.0 to 16.0 wt.% of a second heterophasic propylene ethylene copolymer (HECO2) and 7.0 to 14.0 wt.% of an ethylene polymer (PE).
[0083] In yet another preferred embodiment the heterophasic polypropylene composition (C) comprises 74.0 to 78.0 wt.% of the first heterophasic propylene ethylene copolymer (HECO1), 10.0 to 14.0 wt.% of the second heterophasic propylene ethylene copolymer (HECO2) and 8.0 to 12.0 wt.% of the ethylene polymer (PE).
[0084] In each embodiment the combined amount of the first heterophasic propylene ethylene copolymer (HECO1), the second heterophasic propylene ethylene copolymer (HECO2) and the ethylene polymer (PE) is greater than or equal to 95 wt.-% relative to the total weight of the heterophasic polypropylene composition (C).
[0085] The heterophasic polypropylene composition (C) has a melt flow rate MFR2 measured according to ISO 1133-1 at 230 °C and a load of 2.16 kg in the range of 15.0 to 40.0 g / 10, more preferably in the range of 16.0 to 35.0 g / 10 min, still more preferably in the range of 17.0 to 30.0 g / 10 min, most preferably in the range of 18.0 to 25.0 g / 10 min.
[0086] The heterophasic polypropylene composition (C) has a crystalline fraction (CF) determined according to CRYSTEX QC method ISO 6427-B, which is present in an amount in the range of 77.0 to 95.0 wt.-%, more preferably in the range of 80.0 to 90.0 wt.-%, still more preferably in the range of 82.0 to 88.0 wt.-%, most preferably in the range of 83.0 to 86.0 wt.-%, relative to the total weight of the heterophasic polypropylene composition (C).
[0087] The intrinsic viscosity (IV(CF)) of the crystalline fraction (CF) of the heterophasic polypropylene composition (C) is preferably in the range of 1.00 to 2.00 dl / g, more preferably in the range of 1.20 to 2.00 dl / g, still more preferably in the range of 1.30 to 1.80 dl / g, most preferably in the range of 1.40 to 1.60 dl / g.
[0088] The crystalline fraction (CF) of the heterophasic polypropylene composition (C) preferably has an ethylene content (C2(CF)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 5.0 to 20.0 wt.-%, more preferably in the range of 7.0 to 17.0 wt.-%, still more preferably in the range of 9.0 to 15.0 wt.-%, most preferably in the range of 10.0 to 13.0 wt.-%.
[0089] The heterophasic polypropylene composition (C) has a soluble fraction (SF) determined according to CRYSTEX QC method ISO 6427-B, which is present in an amount in the range of 5.0 to 23.0 wt.-%, more preferably in the range of 10.0 to 20.0 wt.-%, still more preferably in the range of 13.0 to 18.0 wt.-%, most preferably in the range of 15.0 to 17.0 wt.-%, relative to the total weight of the heterophasic polypropylene composition (C).
[0090] The intrinsic viscosity (IV(SF)) of the soluble fraction (SF) of the heterophasic polypropylene composition (C) is preferably in the range of 2.00 to 3.50 dl / g, more preferably in the range of 2.30 to 3.20, still more preferably in the range of 2.50 to 3.00, most preferably in the range of 2.60 to 2.80 dl / g.
[0091] The soluble fraction (SF) of the heterophasic polypropylene composition (C) preferably has an ethylene content (C2(CF)) measured by infrared spectroscopy during CRYSTEX analysis in the range of 25.0 to 50.0 wt.-%, more preferably in the range of 30.0 to 45.0 wt.-%, still more preferably in the range of 33.0 to 40.0 wt.-%, most preferably in the range of 35.0 to 37.0 wt.-%.
[0092] The ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction (IV(SF) / IV(CF)) of the heterophasic polypropylene composition (C) is preferably in the range of 1.40 to 3.00, more preferably in the range of 1.50 to 2.50, still more preferably in the range of 1.60 to 2.20, most preferably in the range of 1.70 to 2.00.
[0093] The total ethylene content (C2) of the heterophasic polypropylene composition (C) is preferably measured in the range of 10.0 to 20.0 wt.-%, more preferably in the range of 12.0 to 18.0 wt.-%, still more preferably in the range of 13.0 to 17.0 wt.-%, most preferably in the range of 14.0 to 16.0 wt.-%.
[0094] It has been found that, while the inclusion of fillers is known to improve the mechanical properties of polypropylene compositions, they have a considerable negative impact on the optical properties of the resulting composition and should therefore be avoided or at least minimized in the context of the present invention.
[0095] The heterophasic polypropylene composition (C) according to the present invention preferably has a low content of mineral fillers. The mineral filler content can be evaluated by measuring the ash content of the heterophasic polypropylene composition (C). Therefore, the ash content of the heterophasic polypropylene composition (C) is preferably less than 2.0 wt.-%, more preferably less than 1.9 wt.-%, still more preferably less than 1.8 wt.-%, most preferably less than 1.7 wt.-%, relative to the gross weight of the heterophasic polypropylene composition (C).
[0096] Even though the mineral filler content is low and the amount of amorphous phase is relatively low the heterophasic polypropylene composition (C) according to this invention has a favourable balance of stiffness and impact strength properties. Furthermore the heterophasic polypropylene composition (C) has a good total light transmittance.
[0097] Accordingly, the heterophasic polypropylene composition (C) according to this invention is characterized by its mechanical properties and light transmittance.
[0098] The total light transmittance of the heterophasic polypropylene composition (C), measured according to ASTM D1003 on 60x60x3 mm injection moulded plaques, is preferably in the range of 40 to 100%, more preferably in the range of 42 to 80%, still more preferably in the range of 44 to 60%, most preferably in the range of 46 to 50%.
[0099] The tensile modulus of the heterophasic polypropylene composition (C) measured according to ISO 527-1.-2 on specimens of tensile type 1B; 170x10x4 mm (ISO 1B) is preferably in the range of 1200 to 2000 MPa, more preferably in the range of 1300 to 1900 MPa, still more preferably in the range of 1400 to 1800 MPa, most preferably in the range of 1500 to 1700 MPa.
[0100] Use of heterophasic polypropylene composition (C) The Charpy notched impact strength at 23°C measured according to ISO 179 1eA of 80x10x4 mm injection moulded bar test specimens prepared according to EN ISO 19069-2 is preferably in the range of 5.0 to 30.0 kJ / m 2In the range of 7.0 to 25.0 kJ / m 2 In the range of 8.0 to 20.0 kJ / m 2 The range is preferably between 9.0 and 15.0 kJ / m 2 within the range.
[0101] Use of heterophasic polypropylene composition (C) The Charpy notched impact strength at -20°C measured according to ISO 179 1eA of 80x10x4 mm injection moulded bar test specimens prepared according to EN ISO 19069-2 is preferably in the range of 3.5 to 20.0 kJ / m 2 In the range of 4.0 to 15.0 kJ / m 2 In the range of 4.5 to 12.0 kJ / m 2 The range is preferably between 5.0 and 10.0 kJ / m 2 within the range.
[0102] The heterophasic polypropylene composition (C) preferably has a puncture energy at 23 °C measured according to ISO 6603-2 using injection moulded plaques of 60x60x3 mm and a test speed of 4.4 m / s in the range of 30.0 to 60.0 J, more preferably in the range of 32.0 to 55.0 J, still more preferably in the range of 34.0 to 50.0 J, most preferably in the range of 36.0 to 45.0 J.
[0103] The heterophasic polypropylene composition (C) preferably has a puncture energy at -20 °C measured according to ISO 6603-2 using injection moulded plaques of 60x60x3 mm and a test speed of 4.4 m / s in the range of 20.0 to 100.0 J, more preferably in the range of 30.0 to 90.0 J, still more preferably in the range of 40.0 to 80.0 J, most preferably in the range of 50.0 to 70.0 J.
[0104] The energy to maximum force of the heterophasic polypropylene composition (C) at 23 °C measured according to ISO 6603-2 using injection moulded plaques of 60x60x3 mm and a test speed of 4.4 m / s is preferably in the range of 15.0 to 40.0 J, more preferably in the range of 18.0 to 35.0 J, still more preferably in the range of 20.0 to 30.0 J, most preferably in the range of 21.0 to 25.0 J.
[0105] The energy to maximum force of the heterophasic polypropylene composition (C) at -20 °C measured according to ISO 6603-2 using injection moulded plaques of 60x60x3 mm and a test speed of 4.4 m / s is preferably in the range of 20.0 to 60.0 J, more preferably in the range of 25.0 to 50.0 J, still more preferably in the range of 30.0 to 45.0 J, most preferably in the range of 35.0 to 40.0 J.
[0106] It is particularly preferred that the balance of properties is maximized. Therefore, it is preferred that the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (I):
[0107]
[0108] The notched impact strength of the simply supported beam was measured at 23°C and expressed in kJ / m 2 express,
[0109] The puncture energy is measured at 23°C and expressed in J.
[0110] The soluble fraction (SF) content is given in % by weight, and
[0111] The total light transmittance is given in %.
[0112] It is further preferred that the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (Ia):
[0113]
[0114] The notched impact strength of the simply supported beam was measured at 23°C and expressed in kJ / m 2 express,
[0115] The puncture energy is measured at 23°C and expressed in J.
[0116] The soluble fraction (SF) content is given in % by weight, and
[0117] The total light transmittance is given in %.
[0118] It is further preferred that the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (Ib):
[0119]
[0120] The notched impact strength of the simply supported beam was measured at 23°C and expressed in kJ / m 2 express,
[0121] The puncture energy is measured at 23°C and expressed in J.
[0122] The soluble fraction (SF) content is given in % by weight, and
[0123] The total light transmittance is given in %.
[0124] Most preferably, the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (Ic):
[0125]
[0126] The notched impact strength of the simply supported beam was measured at 23°C and expressed in kJ / m 2 express,
[0127] The puncture energy is measured at 23°C and expressed in J.
[0128] The soluble fraction (SF) content is given in % by weight, and
[0129] The total light transmittance is given in %.
[0130] It is also preferred that the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (II):
[0131]
[0132] The notched impact strength of the simply supported beam was measured at -20°C and expressed in kJ / m 2 express,
[0133] The puncture energy is measured at -20°C and expressed in J.
[0134] The soluble fraction (SF) content is given in % by weight, and
[0135] The total light transmittance is given in %.
[0136] It is further preferred that the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (IIa):
[0137]
[0138] The notched impact strength of the simply supported beam was measured at -20°C and expressed in kJ / m 2 express,
[0139] The puncture energy is measured at -20°C and expressed in J.
[0140] The soluble fraction (SF) content is given in % by weight, and
[0141] The total light transmittance is given in %.
[0142] It is further preferred that the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (IIb):
[0143]
[0144] The notched impact strength of the simply supported beam was measured at -20°C and expressed in kJ / m 2 express,
[0145] The puncture energy is measured at -20°C and expressed in J.
[0146] The soluble fraction (SF) content is given in % by weight, and
[0147] The total light transmittance is given in %.
[0148] Most preferably, the values of the notched impact strength (NIS), puncture energy, soluble fraction (SF) content and total light transmittance satisfy inequality (IIc):
[0149]
[0150] The notched impact strength of the simply supported beam was measured at -20°C and expressed in kJ / m 2 express,
[0151] The puncture energy is measured at -20°C and expressed in J.
[0152] The soluble fraction (SF) content is given in % by weight, and
[0153] The total light transmittance is given in %.
[0154] Products
[0155] In another aspect the present invention is directed to providing an article comprising the heterophasic polypropylene composition (C).
[0156] In particular, the article according to the invention is an injection-molded article, preferably an automotive article.
[0157] Example
[0158] 1. Definition / determination method:
[0159] Melt flow rate
[0160] The melt flow rate (MFR) is determined according to ISO 1133-1 and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and therefore also of the processability. The higher the melt flow rate, the lower the viscosity of the polymer. The MFR2 of polypropylene is determined at a temperature of 230°C and a load of 2.16 kg. The MFR2 of polyethylene is determined at a temperature of 190°C and a load of 2.16 kg.
[0161] Differential Scanning Calorimetry (DSC)
[0162] Differential scanning calorimetry (DSC) analysis, melting temperature (T m ) and melting enthalpy (H m ), crystallization temperature (T c ) and heat of crystallization (H c ,H CR ) was measured using a TA Instrument Q200 differential scanning calorimetry (DSC) on 5 to 7 mg samples. The DSC was run according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle at a scan rate of 10°C / min over a temperature range of -30 to +225°C. The crystallization temperature (T c ) and heat of crystallization (H c ) is determined by the cooling step, while the melting temperature (T m ) and melting enthalpy (H m ) is determined by the second heating step.
[0163] pass 13 C NMR spectroscopy to quantify polyethylene microstructure
[0164] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content of the polymers.
[0165] for 1 H and 13 C, quantitatively recorded in the melt using a Bruker Avance III500 NMR spectrometer operating at 500.13 and 125.76 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics and all spectra were 13A C-optimized 7 mm magic angle spinning (MAS) probe was recorded at 150° C. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily because of the high sensitivity required for rapid identification and accurate quantification (Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, HW, Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382.; Parkinson, M., Klimke, K., Spiess, HW, Wilhelm, M., Macromol. Chem. Phys. 2007; 208: 2128.; Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50 (2009) 2373; NMR Spectroscopy of Polymers: Innovative Strategies for Complex Macromolecules, Chapter 24, 401 (2011)). Using standard single pulse excitation, transient NOE with a short recycle delay of 3 seconds (Pollard, M., Klimke, K., Graf, R., Spiess, H. W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37: 813.; Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H. W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207: 382.) and RS-HEPT decoupling scheme (Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239.; Griffin, J. M., Tripon, C., Samoson, A., Filip, C., and Brown, S. P., Mag. Res. in Chem. 2007 45, S1, S198). A total of 1024 (1k) transients were acquired for each spectrum. This setting was chosen because it is highly sensitive to low comonomer content.
[0166] Quantitation using custom spectral analysis automation 13 C{ 1H} NMR spectra were processed, integrated and quantitatively characterized. All chemical shifts were internally referenced to the bulk methylene signal (□+) at 30.00 ppm (J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.).
[0167] An exemplary procedure for ethylene octene copolymers is given below.
[0168] Poly(ethylene-co-octene)-octene content
[0169] Characteristic signals corresponding to the incorporation of 1-octene were observed (J. Randall, Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, C29, 201.; Liu, W., Rinaldi, P., McIntosh, L., Quirk, P., Macromolecules 2001, 34, 4757; Qiu, X., Redwine, D., Gobbi, G., Nuamthanom, A., Rinaldi, P., Macromolecules 2007, 40, 6879), and all comonomer contents were calculated relative to all other monomers present in the polymer.
[0170] Characteristic signals arising from isolated 1-octene incorporation (i.e., EEOEE comonomer sequences) were observed. Isolated 1-octene incorporation was quantified using the integral of the signal at 38.37 ppm. This integral was assigned to the unresolved signals of the *B6 and *βB6B6 sites corresponding to isolated 1-octene sequences (EEOEE) and isolated dual non-continuous 1-octene sequences (EEOEOEE), respectively. To compensate for the contribution of the two *βB6B6 sites, the integral of the ββB6B6 site at 24.7 ppm was used:
[0171] O=I *B6+*βB6B6 -2*I ββB6B6
[0172] When a characteristic signal resulting from continuous 1-octene incorporation (EEOOEE) is observed, this continuous 1-octene incorporation is quantified using the integral of the signal at 40.57 ppm assigned to the ααB6B6 site, taking into account the number of reporting sites for each comonomer:
[0173] OO=2*I ααB6B6
[0174] A characteristic signal resulting from discontinuous 1-octene incorporation (i.e., EEOEOEE comonomer sequence) was also observed. This discontinuous 1-octene incorporation was quantified using the integration of the signal at 24.7 ppm assigned to the ββB6B6 site, taking into account the number of reported sites for each comonomer:
[0175] OEO=2*I ββB6B6
[0176] Since no other signals indicative of other comonomer sequences were observed, the total 1-octene comonomer content was calculated based only on the amounts of isolated (EEOEE), dicontinuous (EEOOEE), and discontinuous (EEOEOEE) 1-octene comonomer sequences:
[0177] O 总 =O+OO+OEO
[0178] Characteristic signals arising from saturated end groups were observed. Such saturated end groups were quantified using the average integral of the two resolved signals at 22.84 and 32.23 ppm. The 22.84 ppm integral was assigned to the unresolved signals corresponding to the 2B6 and 2S sites of 1-octene and saturated chain ends, respectively. The 32.23 ppm integral was assigned to the unresolved signals corresponding to the 3B6 and 3S sites of 1-octene and saturated chain ends, respectively. To compensate for the effects of the 2B6 and 3B6 1-octene sites, the total 1-octene content was used:
[0179] S=(1 / 2)*(I 2S+2B6 +I 3S+3B6 -2*O 总 )
[0180] The ethylene comonomer content was quantified using the integration of the bulk methylene (bulk) signal at 30.00 ppm. This integration includes the γ and 4B6 sites from 1-octene as well as the δ + The total ethylene comonomer content is calculated based on the bulk integration and compensated for the observed 1-octene sequences and end groups:
[0181] E 总 =(1 / 2)*[I 本体 +2*O+1*OO+3*OEO+3*S]
[0182] The total mole fraction of 1-octene in the polymer was then calculated as:
[0183] fO=(O 总 / (E 总 +O 总 )
[0184] The total comonomer incorporation of 1-octene in mole percent was calculated from the mole fractions in the standard manner:
[0185] O [mol%] = 100 * fO
[0186] The mole percentage of ethylene incorporation was calculated by the following formula:
[0187] E [mol %] = 100 - O [mol %].
[0188] Dynamic Mechanical Thermal Analysis (DMTA)
[0189] The glass transition temperature Tg is determined by dynamic mechanical thermal analysis (DMTA) according to ISO 6721-7. The measurement is carried out in torsion mode on compression molded samples (40x10x1mm) at a heating rate of 2°C / min between -130°C and +150°C and a frequency of 1Hz. The storage modulus G' is determined according to ISO 6721-7:1996 at +23°C. The measurement is carried out in torsion mode on compression molded samples (40x10x1mm) at a heating rate of 2°C / min between -130°C and +150°C and a frequency of 1Hz.
[0190] Xylene Cold Solubles (XCS)
[0191] The xylene cold soluble fraction (XCS, wt. %) at room temperature is determined according to ISO 16152, 5th edition, 1 July 2005, at 25°C.
[0192] Tensile modulus
[0193] Tensile modulus, tensile strength and tensile strength at break were determined according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min, at 23°C) on 1B specimens.
[0194] Notched Impact Strength (NIS)
[0195] Charpy notched impact strength (NIS) was measured according to ISO 179 1eA at +23°C or -20°C using 80x10x4 mm injection molded bar test specimens prepared according to EN ISO 19069-2.
[0196] Crystal analysis
[0197] Crystallization and Soluble Fraction Methods
[0198] The crystalline (CF) and soluble fractions (SF) of the polypropylene (PP) compositions as well as the comonomer content and the intrinsic viscosity of each fraction were analyzed by CRYSTEX QC, Polymer Char (Valencia, Spain).
[0199] The schematic diagram of the CRYSTEX QC instrument is as follows Figure 1As shown in a. Figure 1 The temperature cycle of dissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160° C., crystallization at 40° C., and redissolution in 1,2,4-TCB at 160° C., as shown in b, separated the crystalline and amorphous fractions. Quantification of SF and CF and determination of ethylene content (C2) were achieved by an infrared detector (IR4), and an online double capillary viscometer was used to determine the intrinsic viscosity (iV).
[0200] The IR4 detector is a multi-wavelength detector that measures two different bands (CH3 stretching vibration (centered at about 2960 cm -1 ) and CH x Extension vibration (2700-3000cm -1 )) can be used to determine the concentration and ethylene content of ethylene-propylene copolymers. The IR4 detector was calibrated using a series of 8 EP copolymers with ethylene contents ranging from 2 wt% to 69 wt% (measured by 13 C-NMR measurement), and various concentrations in the range of 2 and 13 mg / ml respectively. In order to simultaneously consider both the concentration and ethylene content characteristics expected for a variety of polymer concentrations during Crystex analysis, the following calibration equation was applied:
[0201] Concentration = a + b * absorbance (CH) + c * (absorbance (CH) x ))2+d*absorbance(CH3)+e*(absorbance(CH3)2+f*absorbance(CH x )*Absorbance(CH3)(Equation 1)
[0202] CH3 / 1000C=a+b*absorbance(CH x )+c*absorbance(CH3)+d*(absorbance(CH3) / absorbance(CH x ))+e*(absorbance(CH3) / absorbance(CH x ))2(Equation 2)
[0203] Constants a to e of Equation 1 and constants a to f of Equation 2 are determined by using least squares regression analysis.
[0204] The CH3 / 1000C is converted to ethylene content in wt% using the following relationship:
[0205] Weight % (ethylene in EP copolymer) = 100 - CH3 / 1000TC*0.3 (Equation 3)
[0206] The amounts of the soluble fraction (SF) and the crystalline fraction (CF) are related by means of the XS calibration to the amount of "xylene cold solubles" (XCS) and the xylene cold insolubles (XCI) fraction, respectively, determined according to the standard gravimetric method according to ISO 16152. The XS calibration was achieved by testing a number of EP copolymers with an XS content in the range of 2-31 wt%. The determined XS calibration is linear:
[0207] Weight %XS=1.01*weight %SF (Equation 4)
[0208] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online double capillary viscometer and correlated to the corresponding IV determined by the standard method in decalin according to ISO 1628-3. Calibration was achieved using various EP PP copolymers with IV = 2-4 dL / g. The calibration curve determined was linear:
[0209] IV(dL / g)=a*Vsp / c (Equation 5)
[0210] A sample of the PP composition to be analyzed was weighed at a concentration of 10 mg / ml to 20 mg / ml. After automatically filling the vial with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample was dissolved at 160°C with continuous stirring at 400 rpm until completely dissolved, usually for 60 minutes. To avoid sample degradation, the polymer solution was covered with a N2 atmosphere during the dissolution process.
[0211] like Figure 1 As shown in a and b, a certain volume of sample solution is injected into a column filled with an inert carrier, where the sample crystallizes and the soluble fraction is separated from the crystalline part. This process is repeated twice. During the first injection, the entire sample is measured at high temperature, and the IV [dl / g] and C2 [wt%] of the PP composition are determined. During the second injection, the soluble fraction (at low temperature) and the crystalline fraction (at high temperature) as well as the crystallization cycle (wt% SF, wt% C2, IV) are measured.
[0212] based on 13 Determination of C2 content of calibration standards by C NMR spectroscopy
[0213] for 1 H and 13 C, quantitatively recorded in solution using a Bruker Avance III400 NMR spectrometer operating at 400.15 and 100.62 MHz, respectively. 13 C{ 1 H} NMR spectroscopy. Nitrogen was used for all pneumatics and all spectra were taken using13 C was recorded at 125°C using a 10 mm extended temperature probe optimized for C. About 200 mg of the material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium (III) acetylacetonate (Cr(acac)3) to give a 65 mM solution of the relaxant in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, the NMR tube was further heated in a rotating oven for at least 1 hour after initial sample preparation in a heating block. After insertion into the magnet, the tube was rotated at 10 Hz. This setup was chosen primarily for the high resolution and precise ethylene content quantitative quantification required. Standard single pulse excitation was used without NOE, using an optimized tip cone angle, a 1 second recycle delay, and a two-stage WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225, Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were obtained for each spectrum.
[0214] Quantitative 13 C{ 1 H} NMR spectra are processed, integrated, and the relevant quantitative properties are determined from the integration. All chemical shifts are indirectly referenced to the central methylene of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This method allows for comparable references even if this structural unit is not present. Characteristic signals corresponding to ethylene incorporation are observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction is calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer: fE = (E / (P+E). The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) is used by 13 C{ 1The comonomer fraction is quantified by integrating multiple signals across the spectral region in the H} spectrum. This method was chosen for its robustness and ability to account for the presence of regional defects when required. The integration region is fine-tuned to increase applicability over the entire range of comonomer content encountered. For systems with very low ethylene content, where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. is modified to reduce the impact of site integration that no longer exists. This approach reduces the overestimation of the ethylene content of such systems and is achieved by reducing the number of sites used to determine the absolute ethylene content to E = 0.5 (Sββ + Sβγ + Sβδ + 0.5 (Sαβ + Sαγ)). By using this set of sites, using the same symbols in the article by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157), the corresponding integral equation becomes E = 0.5 (I H +I G +0.5(I C +I D )). The equation for absolute propylene content is not modified. The mole percent of comonomer incorporation is calculated from the mole fraction: E[mol %]=100*fE. The weight percent of comonomer incorporation is calculated from the mole fraction: E[wt %]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08)).
[0215] Ash content
[0216] The ash content of a polymer is determined by burning the polymer in a weighed platinum crucible. About 100 grams of polymer are weighed into the crucible. The crucible is then heated in a Bunsen burner flame to allow the polymer to burn slowly. After the polymer has been completely burned, the crucible is cooled, dried and weighed. The ash content is then the weight of the residue divided by the weight of the polymer sample. At least two measurements are made, and if the difference between the two measurements is greater than 7 ppm, a third measurement is made.
[0217] Puncture energy and energy to maximum force
[0218] According to ISO 6603-2, instrumented drop weight test was performed on a 60x60x3mm square made from injection molded plaque. 3The puncture energy and the energy to maximum force are determined on a plate. The test is carried out at 23°C or -20°C (as indicated) using a lubricated tip with a diameter of 20 mm and an impact speed of 4.4 mm / s. Six specimens are tested for each sample, and the six resulting force-deflection curves are used to calculate the average value of the energy to maximum force and the puncture energy. In addition, the impact failure type is also evaluated. ISO6603-2 defines the following impact failure types, and the numbers in brackets are used to calculate the numerical value of the impact failure (the average value obtained from the six test specimens):
[0219] YD yield (zero slope at maximum force) followed by deep drawing (1)
[0220] YS yield (zero slope at maximum force) followed by (at least partially) stable cracking (2)
[0221] YU yield (zero slope at maximum force) followed by unstable cracking (3)
[0222] NY Unyielding (4)
[0223] Total light transmittance and haze
[0224] Optical properties (total light transmittance and haze) of polypropylene in a 60x60x3mm size processed from injection molded plates 3 The test was performed on a plate of ASTM D1003.
[0225] Intrinsic viscosity
[0226] The intrinsic viscosity (iV) is measured according to DIN ISO 1628 / 1 October 1999 in decalin at 135°C.
[0227] 2. Experimental
[0228] a) Polymerization of heterophasic propylene ethylene copolymers
[0229] The heterophasic propylene ethylene copolymers used in the present invention are polymerized using techniques well known in the art using the polymerization conditions given in Table 1.
[0230] The catalyst used for PP1 and PP2 is an emulsion Ziegler-Natta catalyst, which is the same catalyst used in the polymerization of the inventive examples of WO 2017 / 148970 A1.
[0231] The catalyst used for PP3 was Avant ZN180M, supplied by LyondellBasell.
[0232] For each of PP1, PP2 and PP3, the cocatalyst was TEAL and the external donor was dicyclopentyldimethoxysilane (donor D).
[0233] After polymerization under the conditions given in Table 1, standard polypropylene additives were added to the polymer produced in the reactor as shown at the bottom of Table 1 to produce the final added PP1, PP2 and PP3, whose characteristics are given in Table 2.
[0234] Table 1: Polymerization conditions
[0235]
[0236]
[0237] The talc was HM2 manufactured by IMI-Fabi (Italy) with a median particle size d50 of 2.4 μm, a cut-off particle size d95 of 7.7 μm, and a specific surface area of 21 m 2 / g.
[0238] GlySt Glyceryl stearate CAS-No 31556-31-1, commercially available from Danisco (DuPont Group).
[0239] Irganox B 215 A 2:1 blend of Irgafox 168 and Irganox 1010 used as a processing and long-term heat stabilizer, commercially available from BASF SE.
[0240] CaSt Calcium stearate CAS-No 1592-23-0, commercially available from Faci.
[0241] Table 2: Properties of the added heterophasic propylene ethylene copolymers
[0242]
[0243] b) Blended composition
[0244] The inventive and comparative compositions were prepared according to the formulations given in Table 3. Additives were added in the form of a 2.0 wt. % dry blend of additives. The inventive and comparative examples were prepared by melt blending the components in a co-rotating twin-screw extruder Coperion ZSK18. A temperature profile of 20-190-200-220-220-190-170-200° C. from the hopper to the die was applied, with a screw speed of 400 rpm. The polymer melt mixture was discharged and pelletized.
[0245] PP4 is a commercially available automotive polypropylene product EE001AI, available from Borealis AG.
[0246] LDPE is a commercially available low-density polyethylene CA9150 with a melt flow rate MFR2 of 15.0 g / 10 min and a density of 915 kg / m 3 , available from Borealis AG.
[0247] PL is a commercially available ethylene-octene plastomer Queo 0201 with a melt flow rate MFR2 of 1.1 g / 10 min and a density of 902 kg / m 3 , and having a 1-octene content of 4.8 mol %, available from Borealis AG.
[0248] The properties of the final composition are given in Table 4.
[0249] Table 3: Compounded compositions
[0250]
[0251] Talc Jetfine 3CA, with a median particle size d50 of 1.0 μm and a top cut particle size d95 of 3.5 μm, commercially available from Imerys, France
[0252] Songnox 1076SB Octadecyl 3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, CAS-No 2082-79-3, commercially available from Songwon
[0253] Irgafos 168 tris(2,4-di-tert-butylphenyl phosphite), CAS-No 31570-04-4, commercially available from BASF SE
[0254] GlySt Glyceryl Stearate CAS-No 31556-31-1, commercially available from Danisco (DuPont Group)
[0255] CaSt calcium stearate CAS-No 1592-23-0, commercially available from Faci
[0256] MB HC001A-B1, polypropylene produced by Borealis AG, Austria, MFR2 is about 2g / 10
[0257] min, Tm is 160°C, used to prepare the additive dry blend before feeding it.
[0258] Table 4: Properties of Inventive Examples and Comparative Examples
[0259]
[0260] As can be seen from Table 4, the compositions of the present invention have an excellent balance of stiffness, impact properties and optical properties. Considering the relatively low SF content that allows for high stiffness, the compositions of the present invention have surprisingly good impact properties. In addition (although not described in Table 4), all of the inventive examples exhibit only YD yield properties at 23°C, i.e. deep drawing at zero slope at maximum force, which is beneficial for automotive applications. By comparing the inventive examples with CE1, it can be seen that the addition of HECO2 (i.e. PP2 or PP3) and ethylene polymers (i.e. LDPE or PL) leads to improved mechanical properties, especially impact properties. Comparison of IE1 and CE1 shows the detrimental effect of mineral fillers on the optical properties of the composition, indicating that the use of these fillers, which are commonly used to improve mechanical properties, should be avoided. Finally, the compositions of the present invention have optical properties that are superior to similar compositions (i.e. CE3) previously used for similar automotive applications.
Claims
1. A heterophasic polypropylene composition C, comprising: a. 60.0 to 85.0 wt. % of a first heterophasic propylene ethylene copolymer HECO1 having: i. a crystalline fraction CF determined according to the CRYSTEX QC method ISO 6427-B, present in an amount ranging from 75.0 to 92.0% by weight relative to the total weight of HECO1; ii. a soluble fraction SF determined according to CRYSTEX QC method ISO 6427-B, present in an amount ranging from 8.0 to 25.0% by weight relative to the total weight of HECO1; iii. an intrinsic viscosity of the soluble fraction determined according to CRYSTEX QC method ISO 6427-B in the range of 2.00 to 4.00 dl / g; b. 5.0 to 20.0 wt. % of a second heterophasic propylene ethylene copolymer HECO2, which is different from the first heterophasic propylene ethylene copolymer HECO1, having i. a soluble fraction SF determined according to the CRYSTEX QC method ISO 6427-B, present in an amount ranging from 15.0 to 30.0% by weight relative to the total weight of HECO2; ii. an intrinsic viscosity of the soluble fraction measured according to CRYSTEX QC method ISO 6427-B in the range of 2.5 to 5.0 dl / g; and c. 5.0 to 20.0 wt% of an ethylene polymer PE selected from ethylene-based plastomers and LDPE, the ethylene polymer PE having a molecular weight of 895 to 925 kg / m 3 Density within range; wherein the melt flow rate MFR2 measured according to ISO 1133-1 at 230 °C and a load of 2.16 kg of the heterophasic polypropylene composition C is in the range of 15.0 to 40.0 g / 10 min and the soluble fraction SF determined according to CRYSTEX QC method ISO 6427-B of the heterophasic polypropylene composition C is present in an amount in the range of 5.0 to 23.0 wt.-% relative to the total weight of the heterophasic polypropylene composition C, and The total amount of the first heterophasic propylene ethylene copolymer HECO1, the second heterophasic propylene ethylene copolymer HECO2 and the ethylene polymer PE is greater than or equal to 95 wt% relative to the total weight of the heterophasic polypropylene composition C, Wherein the heterophasic polypropylene composition C has an ash content equal to or lower than 2.0 wt.-%.
2. The heterophasic polypropylene composition C according to claim 1, having one or more of the following properties: i. the intrinsic viscosity of the soluble fraction measured according to CRYSTEX QC method ISO 6427-B is in the range of 2.00 to 3.50 dl / g; ii. the ethylene content of the soluble fraction measured by infrared spectroscopy during CRYSTEX analysis is in the range of 25.0 to 50.0 wt. %; iii. the intrinsic viscosity of the crystalline fraction measured according to CRYSTEX QC method ISO 6427-B is in the range of 1.00 to 2.00 dl / g; iv. the ethylene content of the crystalline fraction measured by infrared spectroscopy during CRYSTEX analysis is in the range of 5.0 to 20.0 wt. %; v. the ratio between the intrinsic viscosity of the soluble fraction measured according to CRYSTEX QC method ISO 6427-B and the intrinsic viscosity of the crystalline fraction measured according to CRYSTEX QC method ISO 6427-B is in the range of 1.40 to 3.00; and vi. The total ethylene content C2 measured by infrared spectroscopy during CRYSTEX analysis is in the range of 10.0 to 20.0 wt.-%.
3. The heterophasic polypropylene composition C according to claim 1, wherein the first heterophasic propylene ethylene copolymer HECO1 has one or more of the following properties: i. the ethylene content of the soluble fraction measured by infrared spectroscopy during CRYSTEX analysis is in the range of 20.0 to 60.0 wt. %; ii. the intrinsic viscosity of the crystalline fraction measured according to CRYSTEX QC method ISO 6427-B is in the range of 1.00 to 2.00 dl / g; iii. the ethylene content of the crystalline fraction measured by infrared spectroscopy during CRYSTEX analysis is in the range of 0.5 to 5.0 wt. %; and iv. the ratio between the intrinsic viscosity of the soluble fraction measured according to CRYSTEX QC method ISO 6427-B and the intrinsic viscosity of the crystalline fraction measured according to CRYSTEX QC method ISO 6427-B is in the range of 1.00 to 3.
00.
4. The heterophasic polypropylene composition C according to claim 1, wherein the first heterophasic propylene ethylene copolymer HECO1 has one or more of the following properties: i. a melt flow rate MFR2 measured at 230°C and a load of 2.16 kg in accordance with ISO 1133-1 in the range of 15.0 to 50.0 g / 10 min; and ii. The total ethylene content C2 measured by infrared spectroscopy during CRYSTEX analysis is in the range of 3.0 to 15.0 wt.-%.
5. The heterophasic polypropylene composition C according to claim 1, wherein the second heterophasic propylene ethylene copolymer HECO2 has one or more of the following properties: i. a melt flow rate MFR2 measured at 230°C and a load of 2.16 kg in accordance with ISO 1133-1 in the range of 1.0 g / 10 min to 20.0 g / 10 min; ii. a total ethylene content C2 in the range of 8.0 to 15.0 wt. % as measured by infrared spectroscopy during CRYSTEX analysis; iii. the ethylene content of the soluble fraction measured by infrared spectroscopy during CRYSTEX analysis is in the range of 20.0 to 60.0 wt. %; iv. the intrinsic viscosity of the crystalline fraction measured according to CRYSTEX QC method ISO 6427-B is in the range of 1.00 to 2.50 dl / g; v. the ethylene content of the crystalline fraction measured by infrared spectroscopy during CRYSTEX analysis is in the range of 0.5 to 7.0 wt. %; as well as vi. The ratio between the intrinsic viscosity of the soluble fraction and the intrinsic viscosity of the crystalline fraction, determined according to CRYSTEX QC method ISO 6427-B, is in the range of 1.00 to 2.
50.
6. Heterophasic polypropylene composition C according to anyone of claims 1 to 5, wherein the ratio of the melt flow rates MFR2 measured according to ISO 1133-1 at 230 °C and a load of 2.16 kg of the first heterophasic propylene ethylene copolymer HECO1 and the second heterophasic propylene ethylene copolymer HECO2 is at least 2.
0.
7. The heterophasic polypropylene composition C according to anyone of claims 1 to 5, wherein the ethylene polymer PE has a melt flow rate MFR2 measured according to ISO 1133-1 at 190 °C and a load of 2.16 kg in the range of 0.5 to 30.0 g / 10 min.
8. The heterophasic polypropylene composition C according to any one of claims 1 to 5, wherein the ethylene polymer PE is an ethylene-based plastomer PL, wherein the ethylene-based plastomer has one or more of the following properties: i. a melt flow rate MFR2 measured at 190°C and a load of 2.16 kg in accordance with ISO 1133-1 in the range of 0.5 g / 10 min to 10.0 g / 10 min; ii. Density between 895 and 908 kg / m 3 within the scope of iii. comonomers selected from C3 to C10 α-olefins; and iv. Through quantitative 13 The comonomer content measured by C-NMR analysis was in the range of 3.0 to 6.0 mol%.
9. The heterophasic polypropylene composition C according to any one of claims 1 to 5, wherein the ethylene polymer PE is a low density polyethylene LDPE, wherein the low density polyethylene has one of the following properties: i. a melt flow rate MFR2 measured at 190°C and a load of 2.16 kg in accordance with ISO 1133-1 in the range of 10.0 g / 10 min to 30.0 g / 10 min; and ii. Density between 908 and 925 kg / m 3 between.
10. The heterophasic polypropylene composition C according to anyone of claims 1 to 5 having a total light transmittance in the range of 40 to 100% measured according to ASTM D1003 on 60x60x3 mm injection molded plaques.
11. The heterophasic polypropylene composition C according to any one of claims 1 to 5, having one or more of the following properties: i. The tensile modulus measured on a specimen of 170 x 10 x 4 mm in a tensile type 1B according to ISO 527-2 is in the range of 1200 to 2000 MPa; ii. Charpy notched impact strength at 23°C measured according to ISO 179 1eA using 80 x 10 x 4 mm injection molded bar test specimens prepared according to EN ISO 19069, in the range of 5.0 to 30.0 kJ / m 2 within the scope of iii. Charpy notched impact strength at -20°C measured according to ISO 179 1eA using 80 x 10 x 4 mm injection molded bar test specimens prepared according to EN ISO 19069 is between 3.5 and 20.0 kJ / m 2 within the scope of iv. The puncture energy at 23°C measured in accordance with ISO 6603-2 using a 60 x 60 x 3 mm injection molded plaque and a test speed of 4.4 m / s is in the range of 30.0 to 60.0 J; v. Puncture energy in the range of 20.0 to 100.0 J at -20°C measured according to ISO 6603-2 using a 60 x 60 x 3 mm injection molded plaque and a test speed of 4.4 m / s; vi. Energy to maximum force at 23°C in the range of 15.0 to 40.0 J measured according to ISO 6603-2 using a 60 x 60 x 3 mm injection molded plaque and a test speed of 4.4 m / s; and vii. Energy to Maximum Force at -20°C measured according to ISO 6603-2 using a 60 x 60 x 3 mm injection moulded plaque and a test speed of 4.4 m / s is in the range of 20.0 to 60.0 J.
12. The heterophasic polypropylene composition C according to anyone of claims 1 to 5, wherein the values of Charpy notched impact strength, puncture energy, soluble fraction SF content determined according to CRYSTEX QC method ISO 6427-B and total light transmittance satisfy inequality (I): The notched impact strength is measured at 23°C and expressed in kJ / m 2 express, The puncture energy is measured at 23°C and expressed in J. The soluble fraction SF content is given in % by weight, and The total light transmittance is given in %.
13. The heterophasic polypropylene composition C according to anyone of claims 1 to 5, wherein the values of Charpy notched impact strength, puncture energy, soluble fraction SF content determined according to CRYSTEX QC method ISO 6427-B and total light transmittance satisfy inequality (II): The notched impact strength is measured at -20°C and expressed in kJ / m 2 express, The puncture energy is measured at -20°C and expressed in J. The soluble fraction SF content is given in % by weight, and The total light transmittance is given in %.
14. Injection moulded article comprising the heterophasic polypropylene composition C according to any of the preceding claims 1 to 13.
15. The injection molded article according to claim 14, wherein the injection molded article is an automotive article.
Citation Information
Patent Citations
Propylene polymer compositions
EP2480606A1
Clear and impact resistant polymer composition and fabricated article
WO2017117054A1
High flow heterophasic polyolefin composition having improved stiffness / impact balance
WO2017148970A1
Polypropylene compositions for automotive applications
CN108137889A